GLUD1 suppresses renal tumorigenesis and development via inhibiting PI3K/Akt/mTOR pathway - Wang, Lei; Fang, Zhiyu; Gao, Peixiang; Zheng, Junfang (Frontiers in Oncology, 2022)
Growing cancer cells are addicted to glutamine. Glutamate dehydrogenase 1 (GLUD1) is one of key enzymes in glutamine metabolism and plays a critical role in the malignancy of diverse tumors. However, its role and molecular mechanism in clear cell renal cell carcinoma (ccRCC) development and progression remain unknown. In this study, analysis results of the GEO/TCGA/UALCAN database showed that GLUD1 level was downregulated in ccRCC tissues. Immunohistochemistry and western blotting results further validated the downregulation of GLUD1 level in ccRCC tissues. GLUD1 level was gradually decreased as ccRCC stage and grade progressed. Low GLUD1 level was associated with a shorter survival in ccRCC, reminding that GLUD1 level could predict the prognosis of ccRCC patients. High level of methylation in GLUD1 promoter was positively correlated with the downregulation of GLUD1 level and was negatively correlated with survival of ccRCC patients. GLUD1 overexpression suppressed RCC cell proliferation, colony formation and migration by inhibiting PI3K/Akt/mTOR pathway activation. Together, we found a novel tumor-suppressing role of GLUD1 in ccRCC which was different from that in other tumors and a new mechanism for inhibiting PI3K/Akt/mTOR activation in ccRCC. These results provide a theoretical basis for GLUD1 as a therapeutic target and prognostic marker in ccRCC.